What's the opposite of a zero?

Algebra Level 3

Find the sum of all real x x values which satisfy:

1 x 2 6 x + 10 + x 2 + x x 4 + 3 x 2 + x + 1 + 1 x 2 + x + 1 0 \left\lfloor\dfrac{1}{x^2-6x+10}\right\rfloor+\left\lfloor\dfrac{x^2+x}{x^4+3x^2+x+1}\right\rfloor+\left\lfloor\dfrac{1}{x^2+x+1}\right\rfloor\not=0

Notation: \lfloor \cdot \rfloor denotes the floor function .


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Braden Dean
Dec 23, 2020

Let:

f ( x ) = 1 x 2 6 x + 10 f(x)=\left\lfloor\dfrac{1}{x^2-6x+10}\right\rfloor

g ( x ) = x 2 + x x 4 + 3 x 2 + x + 1 g(x)=\left\lfloor\dfrac{x^2+x}{x^4+3x^2+x+1}\right\rfloor

h ( x ) = 1 x 2 + x + 1 h(x)=\left\lfloor\dfrac{1}{x^2+x+1}\right\rfloor

We can rewrite 1 x 2 6 x + 10 \dfrac{1}{x^2-6x+10} as 1 ( x 3 ) 2 + 1 \dfrac{1}{(x-3)^2+1}

We can see that for all x 3 x\not=3 , 1 x 2 6 x + 10 > 0 \dfrac{1}{x^2-6x+10}>0 as ( x 3 ) 2 + 1 > 1 (x-3)^2+1 > 1

At x = 3 x=3 , 1 x 2 6 x + 10 = 1 \dfrac{1}{x^2-6x+10} = 1 as ( x 3 ) 2 + 1 = 1 (x-3)^2+1=1

Therefore, f ( x ) = { 0 x 3 1 x = 3 } f(x) = \left\{\begin{array}{lr} 0 & x\not=3 \\ 1 & x=3 \end{array}\right\}

We can rewrite x 2 + x x 4 + 3 x 2 + x + 1 \dfrac{x^2+x}{x^4+3x^2+x+1} as x ( x + 1 ) ( x 2 + 1 ) 2 + x ( x + 1 ) \dfrac{x(x+1)}{(x^2+1)^2+x(x+1)}

We can see that the zeros occur at x = 1 x=-1 and x = 0 x=0 , with the function negative over 1 < x < 0 -1<x<0

Setting equal to 1:

x ( x + 1 ) ( x 2 + 1 ) 2 + x ( x + 1 ) = 1 \dfrac{x(x+1)}{(x^2+1)^2+x(x+1)} = 1

x ( x + 1 ) = ( x 2 + 1 ) 2 + x ( x + 1 ) x(x+1) = (x^2+1)^2+x(x+1)

( x 2 + 1 ) 2 = 0 (x^2+1)^2 = 0

No solution

Setting equal to -1:

x ( x + 1 ) ( x 2 + 1 ) 2 + x ( x + 1 ) = 1 \dfrac{x(x+1)}{(x^2+1)^2+x(x+1)} = -1

x ( x + 1 ) = ( x 2 + 1 ) 2 x ( x + 1 ) x(x+1) = -(x^2+1)^2-x(x+1)

( x 2 + 1 ) 2 + 2 x ( x + 1 ) = 0 (x^2+1)^2 +2x(x+1) = 0

Minimum of ( x 2 + 1 ) 2 (x^2+1)^2 is 1, and minimum of 2 x ( x + 1 ) 2x(x+1) is 1 2 -\frac{1}{2} , therefore:

No solution

We now know that 1 < x 2 + x x 4 + 3 x 2 + x + 1 < 1 -1<\dfrac{x^2+x}{x^4+3x^2+x+1}<1

Therefore, g ( x ) = { 0 x 1 1 1 < x < 0 0 x 0 } g(x) = \left\{ \begin{array}{lr} 0 & x\le-1 \\ -1 & -1<x<0 \\ 0 & x\ge0 \end{array}\right\}

Finally,

1 x 2 + x + 1 > 0 \dfrac{1}{x^2+x+1} > 0 for all x

Setting equal to 1:

1 x 2 + x + 1 = 1 \dfrac{1}{x^2+x+1} = 1

x 2 + x + 1 = 1 x^2+x+1 = 1

x 2 + x = 0 x^2 + x = 0

x = 1 x=-1 and x = 0 x=0

Setting equal to 2:

1 x 2 + x + 1 = 2 \dfrac{1}{x^2+x+1} = 2

2 x 2 + 2 x + 2 = 1 2x^2+2x+2 = 1

2 x 2 + 2 x + 1 = 0 2x^2+2x+1 = 0

Minimum of 2 x 2 + 2 x + 1 2x^2+2x+1 is 1 2 \frac{1}{2} , therefore,

No solution

Therefore, h ( x ) = { 0 x < 1 1 1 x 0 0 x > 0 } h(x) = \left\{\begin{array}{lr} 0 & x<-1 \\ 1 & -1\le x \le 0 \\ 0 & x>0 \end{array}\right\}

Looking at these three functions we can see that their sum is equal to 0 everywhere except x = 1 x=-1 , x = 0 x=0 , and x = 3 x=3 , where it's equal to 1.

Therefore, the answer is 1 + 0 + 3 = 2 -1 + 0 + 3 = \fbox{2}

This is such an interesting question. Very creative!

Elijah L - 5 months, 2 weeks ago

Log in to reply

Thanks! I really appreciate it!

Braden Dean - 5 months, 2 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...